The Influence of Workload, Motivation, Commitment and Compliance on the Performance of Health Workers at Surakarta Islamic Hospital - Muhammad Nahar Sarwani; Istiatin Istiatin; Yunia Wahdiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the influence of Workload, Motivation, Commitment, and Compliance on the performance of healthcare workers at Surakarta Islamic Hospital. The data analysis techniques utilized include Classical Assumption Tests (normality test, multicollinearity test, heteroscedasticity test) and Statistical Tests (multiple linear regression analysis, collinearity test, hypothesis testing, and the coefficient of determination), processed using SPSS software. Based on the results of the hypothesis testing, it can be concluded that Workload, Motivation, Commitment, and Compliance have a positive and significant effect on the performance of healthcare workers at Surakarta Islamic Hospital. Keywords: workload, motivation, commitment, compliance, healthcare worker performance